Association between TNF-α gene polymorphisms and susceptibility of myelodysplastic syndromes: a meta-analysis. Issue 1 (1st January 2021) - Zhou, Tao; Yin, Sun-Jun; Wang, Ping; Fan, Yu-Xin; Li, Zhi-Ran; Yang, Qin; Huang, Yan-Hua; Meng, Rui; He, Gong-Hao
ABSTRACT: Objective: Myelodysplastic syndromes (MDS) constitute a heterogeneous group of clonal hematological diseases. Previous investigations reported that tumor necrosis factor-alpha (TNF-α) gene polymorphisms were associated with MDS susceptibility, but the results remained controversial. Thus, we conducted a meta-analysis to higher elucidate the correlation between TNF-α gene polymorphisms and MDS susceptibility. Methods: The PubMed, Cochrane Library, Embase, Chinese National Knowledge Infrastructure (CNKI), and Wan Fang databases were searched for eligible literatures published up to July 2021. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were applied to evaluate the strength of association. Results: Eight studies involving 1180 MDS patients and 1387 controls were included in this meta-analysis. For the TNF-α G308A polymorphism, we confirmed that the G allele (G versus A: P  = 0.001), GG genotypes (GG versus GA: P  = 0.005; GG versus GA + AA: P  = 0.002), and GG + AA genotypes (GG + AA versus GA: P  = 0.008) was significantly associated with decreased MDS susceptibility according to different genetic models. Furthermore, the G308A polymorphism was significantly correlated with decreased occurrence risk of MDS in the Caucasian population as compared with Asians in the above four genetic models ( P  < 0.05). However, no significant association was observed between the TNF-α G238A polymorphism and MDS risk. Conclusion: This research showed that TNF-α G308A polymorphism might be a potential biomarker in early clinical screening of MDS, which would contribute to improving the individualized prevention of MDS patients in clinic.